2016
DOI: 10.4103/0974-8237.176625
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral lag-screw technique for an isolated anterior 1/4 atlas fracture

Abstract: Study Design:Fractures of the atlas are classified based on the fracture location and associated ligamentous injury. Among patients with atlas fractures treated using external immobilization, nonunion of the fracture could be seen.Objective:Ideally, treatment strategy for an unstable atlas fracture would involve limited fixation to maintain the fracture fragments in a reduced position without restricting the range of motion (ROM) of the atlantoaxial and atlantooccipital joints.Summary of Background Data:Such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The literature mainly recommends conservative treatment for isolated fractures of the lateral masses [10]. However, recent studies observed frequently a lateral displacement of the lateral mass fragments associated with subluxation of the occipital condyle resulting in neck pain, head malposition and impaired head rotation [17]. Hence, some guidelines advocate for surgery in Gehweiler 4 fractures with joint incongruency [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…The literature mainly recommends conservative treatment for isolated fractures of the lateral masses [10]. However, recent studies observed frequently a lateral displacement of the lateral mass fragments associated with subluxation of the occipital condyle resulting in neck pain, head malposition and impaired head rotation [17]. Hence, some guidelines advocate for surgery in Gehweiler 4 fractures with joint incongruency [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, a unilateral lag screw osteosynthesis has been described in oblique fracture patterns without comminution. 22 In temporary occipito-cervical stabilizations the implants should be removed after bony healing of the atlas fracture to allow for regaining motion. In case of an inadequate healing and an occipito-atlantal or atlanto-axial joint incongruity under halo-traction resulting in a symptomatic nonunion, fusion of the affected motion segments is recommended to prevent the patient from persistent pain caused by posttraumatic arthritis.…”
Section: Therapeutic Algorithm ( Figure 3 )mentioning
confidence: 99%
“…The lag-screw principle in combination with anti-rotational plates is common in long-bone fractures, as lag-screws reduce the threat of a non-union. However, besides case reports dealing with cervical spine fractures, 26 this principle has no relevance in spine surgery so far. Obviously, a lag-screw osteosynthesis is out of the question in most vertebral fractures; however, keeping in mind the fracture-morphology both split and pincer fractures could benefit from this treatment.…”
Section: Discussionmentioning
confidence: 99%